KEBENARAN MENURUT PRAGMATISME DAN TANGGAPANNYA TERHADAP ISLAM - Fauziah Nurdin (Universitas Islam Negeri Ar-Raniry, 2014)
A pragmatism school of philosophy is flourished in America in the late 19th century AD. As a school of philosophy, pragmatism tries to mediate a tradition which was developed by the empiricists to the tradition which was developed by the idealists. According to pragmatism truth is an efficient, and useful, although it is relative. The truth in pragmatism is of course different from the truth of Islam. In Islam, the truth is something that is absolute, as the source of truth is God’s revelation, not the rational of human analogies.